Archaeologies of Totalitarianism, Authoritarianism, and Repression
XXII, 241 p. 30 illus., 26 illus. in color.
Keywords: "This volume offers detailed case studies that apply the approach of contemporary archaeology to investigate and expose ways in which the repressive actions and policies of authoritarian and totalitarian regimes affect peoples’ everyday lives, bodies, mobilities, memory-making, and heritage construction. The volume is wide in its scope; it is a timely and original contribution to the growing field of scholarship on the material residues of the discomfiting aspects of heritage." -Mary C. Beaudry, Boston University, USA This book offers new insights into the mechanisms of state control, systematic repression, and mass violence focused on ethnic, political, class, and religious minorities in the recent past. The geographical and temporal scope of the volume breaks new ground as international scholars foreground how contemporary archaeology can be used to enhance the documentation and interpretation of totalitarian and authoritarianregimes, to advance theoretical approaches to atrocities, and to broaden public understandings of how such regimes use violence and repression to hold on to power. James Symonds is Professor of Historical Archaeology at the University of Amsterdam. His research interests focus on global historical and contemporary archaeology, and his recent projects have included work on urban archaeology; conflict archaeology; the archaeology of Diasporic communities; and archaeologies of poverty and inequality. Pavel Vařeka is Associate Professor and Head of the Department of Archaeology at the University of West Bohemia in Pilsen. His recent work has focused on later medieval, post-medieval, and modern settlement archaeology; building archaeology; ‘campscape’ archaeology; and archaeologies of communism. He has also led archaeological expeditions to the North Caucasus and Kyrgyzstan.